2022
DOI: 10.1055/a-1933-3592
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anatomical Variations with Morphological Measurements and Their Relationship to Meniscal Injury and Ligament Damage

Abstract: Introduction: The purpose of this study was to reveal the anatomical risk factors for anterior and posterior cruciate ligament (ACL and PCL) injuries and menisci injury. We aim to investigate whether there are significant relationship between tibial tubercle-trochlear groove distance distance (TT-TG), patella angle, trochlear sulcus angle (TSA), trochlear groove depth (TGD), medial and lateral trochlea length (MT and LT), MT/LT ratio, lateral patellar tilt angle (LPTA), patella-patellar tendon angle (P-PTA), q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…They reported that larger QPA is increasing the frequency of total anterior cruciate ligaman tear. However larger QPA did not increase the menisci tear ( 21 ). The meniscus distributes the pressure transmitted to the main joint to the knee joint surface and absorbs shock in case of excessive loading.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…They reported that larger QPA is increasing the frequency of total anterior cruciate ligaman tear. However larger QPA did not increase the menisci tear ( 21 ). The meniscus distributes the pressure transmitted to the main joint to the knee joint surface and absorbs shock in case of excessive loading.…”
Section: Discussionmentioning
confidence: 89%
“…QPA is a newly discovered angle showing the axis of the vectorial sum of the forces on the patella. As the QPA changes, the force transmitted to the patella also changes ( 21 ). Recently, there are only few studies evaluated the QPA ( 4 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations